(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Enhancing customer loyalty has become a significant concern for several organisations due to the increased competition in the industries. The Indian Telecommunication Industry has experienced a major shift after the launch of Reliance JIO. Many customers have been attracted to Reliance JIO, but it is important for this company to transform the existing customers into loyal customers. The objective of the research is to identify the factors that may increase the brand loyalty of the customer in this industry. To reach this objective the following tasks were set: (1) to research scientific literature on customer loyalty, in general, and in the sphere of telecommunications, in particular; (2) to work out research methodology; (3) to carry out empirical research and discuss results. The research question: What are the factors that can enhance the customer loyalty in the telecommunication industry? Data is collected via customer survey (n=250) and processed by SPSS. The main result of the research lies in the developed customer loyalty framework for telecommunication companies. Practical significance of results lies in recommendations how to enhance customer loyalty towards Reliance Jio Infocomm, Ltd.